Development of Learning Videos for State Administration Law Courses as a Hybrid Learning Solution at FHISIP University of Mataram - Evangelista, Beverly; Daulay, R. Fahmi Natigor; Mulyana, Septira Putri; Sumaragatha, I Gusti Bagus Sakah (Abdi Masyarakat, 2025)
Digital transformation in higher education requires learning innovations that are adaptive to the characteristics of the millennial generation, especially in complex courses such as State Administration Law (HAN). At FHISIP University of Mataram, conventional lecture methods still dominate, causing boredom and low understanding of students to abstract concepts such as the principle of legality and discretion of public officials. Responding to these challenges, this service project developed VIP-HAN (Innovative Video of Learning Law of State Administration) as an interactive and easily accessible technology-based learning media. The implementation method consists of six stages: consultation with mentors, coordination with the Head of the Constitutional Law Section, collection of materials, video production using CapCut and Canva applications, socialization in class, and evaluation through Google Form questionnaires. The video material is compiled based on RPS and academic literature, with a storytelling approach and infographic animation to make it easier to understand. The evaluation showed that 85% of students found it helpful to understand abstract concepts, and 78% of lecturers appreciated the efficiency of teaching time. The discussion included technical challenges, adaptive strategies, and cross-disciplinary collaboration in content development. The project also sparked further innovations in the faculty environment, such as the development of podcasts and digital simulations by other study programs. In conclusion, VIP-HAN has proven to be effective as a hybrid learning solution that supports the digitization of legal education. Institutional support and strengthening of lecturer capacity are the key to the sustainability of this innovation in the future.